Synthesis and biological evaluation of a new series of cinnamic acid amide derivatives as potent haemostatic agents containing a 2-aminothiazole substructure. Issue 18 (15th September 2017) - Nong, Wenqian; Zhao, Anran; Wei, Jinrui; Lin, Xiao; Wang, Lisheng; Lin, Cuiwu
Graphical abstract: This study demonstrates the use of new compoundN5 with potential characteristics for the development of drugs combining coagulant and platelet activities. Abstract: Ten new cinnamic acid derivatives containing a 2-aminothiazole substructure were designed and synthesized. This series of compounds exhibited good thermostabilities as demonstrated by thermogravimetric analysis. In coagulation assays (prothrombin time, activated partial thromboplastin time and thrombin time) in vitro, most compounds demonstrated excellent activities to promote blood coagulation. Among the studied series, compoundsN1, N4, N5 andW5 exhibited a significant coagulation activity. Further studies indicated that compoundN5 (IC50 = 1.87 μmol/L) displayed the most suitable efficacy of promoting platelet aggregation than the clinically used haemostatic drug etamsylate (IC50 = 46.22 μmol/L). Furthermore, the relationship between the functional groups of the compounds and the corresponding blood coagulant activity was explored in this study.